PENGARUH KINERJA KEUANGAN, UKURAN PERUSAHAAN, DAN KEPEMILIKAN SAHAM TERHADAP KINERJA LINGKUNGAN PADA PERUSAHAAN PERTAMBANGAN DI BURSA EFEK INDONESIA - Anditto Farlinno; Yustrida Bernawati (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Abstract. This research aims to determine the effect of financial performance, firm size, and share ownership on environmental performance based on the Environmental Performance Rating Program in Environmental Management (PROPER) at mining companies listed on the Indonesia Stock Exchange (BEI) in 2012 to 2016. This research uses quantitative method. The population in this research are 41 mining sector companies listed on the Stock Exchange and the number of samples in this research are 36 selected using purposive sampling method. The hypothesis in this research are tested using multiple linear regression. The results of this research indicate that profitability and firm size have a significant effect on PROPER-based environmental performance, while liquidity and share ownership have no significant effect on PROPER-based environmental performance.